A novel architecture of single-arm duobinary direct modulation format for optical communication - Lee, L.H.; Geok, T.K.; Reza, A.W. (Natl Inst Optoelectronics, 2010)
Recent trend have shown that the growth of internet traffic has accentuated the aggravating lag of access network capacity and most widely deployed broadband solutions are unable to provide enough bandwidth for the emerging services. A new technology is required that is inexpensive, simple, scalable, and capable of handling above mentioned fundamental constraints in high-speed communication systems. The optical duobinary coding is an effective method in high-speed transmission systems to increase the dispersion tolerance, to improve the spectral efficiency, and to reduce the sensitivity of non-linear effects. Therefore, a novel and simple (alternative) duobinary precoder is presented in this paper using standard logic ICs for the configuration of duobinary single-arm direct modulation transmitter. The performance of the proposed single-arm duobinary direct modulation format is evaluated by comparing the bit-error-rate (BER), eye diagram, and Q value with different bit rates. The obtained results show satisfactory performance and good agreement with the simulated results.